TYPES OF LITERACY LEARNING IN EARLY GRADES: WHAT DOES THE TEACHER DO? - Maulani, Susan; Musthafa, Bachrudin; Damaianti, Vismaia S; Agustin, Mubiar (PrimaryEdu : Journal of Primary Education, 2021)
Literacy has become a major component of learning. In early elementary schools, children must be taught early reading skills to build a higher grades literacy foundation. The teacher determines literacy learning performance in the classroom because it plays a vital role in the front line of learning. The main objective of this research was to describe the process of learning literacy in elementary schools. This study used a survey method involving five principals and thirty elementary school teachers. Interviews were used as instruments to describe literacy learning in elementary school. Data obtained from the field were tabulated and presented. This study showed that the methods or models and learning media used by the teacher were different. The teacher had also shown an effort to increase children's motivation in participating in literacy learning.Keywords: Early literacy, early grade elementary school, elementary school teachers.